Comportamiento agronómico del cultivo de pepino (Cucumis sativus L.) con diferentes abonos orgánicos en la Unidad Educativa Calazacón del cantón Santo Domingo de los Tsachilas, año 2014. - Quille Naula, Freddy José (2015)
This research was conducted at the Education Unit of the Canton Calazacón Santo Domingo de los Tsáchilas, 2014. Located at Km 6 ½ Road Santo Domingo - Quevedo left margin; belonging to the Canton Santo Domingo, Santo Domingo Province of Tsáchilas. With a geographic location 13'50'' 0 ° South latitude, 79 ° west longitude 10'40'' and 495 meters, the investigation lasted 80 days. The jurisdiction treatments: T1 = 1kg of humus / m2 T2 = 3 kg of humus / m2 humus T3 = 5kg / m2 T4 = 1kg water hyacinth / m2 T5 = 3 kg of water hyacinth / m2 T6 = 5kg Jacinto water / m2 and T7 = Control / m2. The experimental design was RCBD with seven treatments and four repetitions. The variables evaluated were: plant height, stem diameter, number, diameter and weight of fruits, yield per plot. The results shown in research highlights the biggest result in plant height (cm); Stem diameter (cm); Length of fruit (cm); Fruit diameter (cm) and fruit weight at 15, 30 and 45 days received treatment 3 with a dosage of 5 kg of humus The increased production in kg m2 plot kg, treatment and reflex hectare per ton in the treatment 3 with the dosage of 5 kg of humus with 19.57 kg; 18.42 kg; 73.68 kg and 83.73 ton The economic analysis of the treatments under study at cost, which were $ 30.43 in the case of treatment 1; $ 33.07 for 2; $ 35.72 to 3; $ 30.38 in the 4; $ 32.94 for the 5; $ 35.50 for 6 and $ 26.60 for the witness, higher income 106.47 USD. The most useful treatment met 3 to 5 kg dosage humus with $ 70.76. The best cost / benefit ratio to treatment was 3 to 5 kg dosage humus with $ 0.33